The quadratic formula is given by:
x = (-b ± √(b^2 - 4ac)) / (2a)
For the equation -2x^2 - 7x + 13 = 0, we have a = -2, b = -7, and c = 13. Substituting these values into the quadratic formula, we get:
x = (-(-7) ± √((-7)^2 - 4(-2)(13))) / (2(-2))
x = (7 ± √(49 + 104)) / (-4)
x = (7 ± √(153)) / (-4)
Therefore, the solutions to the quadratic equation -2x^2 - 7x + 13 = 0 are:
x = (7 + √(153)) / (-4) and x = (7 - √(153)) / (-4)
Solve the following quadratic equation using the quadratic formula.
−2x2−7x+13=0
−
2
�
2
−
7
�
+
13
=
0
**Note: Make sure to enter both solutions together in the space provided using the ±
±
symbol.
For example: x={12±10−−√}
�
=
{
1
2
±
10
}
(If you need help with this, reach out to your teacher.)
(1 point)
x=
�
=
{
}
1 answer